Newly isolated yeasts from Tunisian microhabitats: Lipid accumulation and fatty acid composition. Issue 3 (30th March 2016) - Arous, Fatma; Azabou, Samia; Triantaphyllidou, Irene‐Eva; Aggelis, George; Jaouani, Atef; Nasri, Moncef; Mechichi, Tahar
Abstract : Newly isolated yeasts from different Tunisian microhabitats, such as soil, milk, olive brine, vinegar, and from olive mill wastewater‐contaminated biotopes were extensively studied for their biochemical arsenal and morphological features, i.e. cell, ascospore, and lipid body morphology. All strains were classified into the Ascomycota phylum. However, they showed great functional diversity, including different morphological and biochemical features, lipid production ability, and fatty acid profiles. Accordingly, the strains were placed in three different groups: Group I, which includes Candida species; Group II ( Pichia and related); and Group III ( Kluyveromyces marxianus strain CC1). Group I and II were characterized by a high percentage of oleic acid (41.6–65.3% of total lipids) while in Group III, linoleic acid was the major fatty acid (37.2%). Members of Group I and II were further grouped into subgroups according to their fatty acid composition. Among the newly isolated strains, Pichia etchellsii BM1 was able to accumulate around 25% wt/wt lipid per dry cell mass and thus characterized as oleaginous. Some other strains, such as Candida metapsilosis strain EL2, C. parapsilosis strain LV2, C. pararugosa strain BM24, and K. marxianus strain CC1, which are able to produce extracellular lipases, may be of interest for specific environmental applications and/or for the production of novel lipases.